The Impact of Adaptive Pricing on the Competitiveness of Small Companies in Online Commerce - Rohach, Yaroslav (Актуальні питання економічних наук, 2025)
The relevance of the study is due to the need to adapt small enterprises to the current conditions of online commerce, where adaptive pricing is becoming an important tool for increasing competitiveness in conditions of limited resources and high competition. The article provides a scientific justification for the impact of adaptive pricing on increasing the competitiveness of small enterprises in online commerce, taking into account the technological, economic and behavioral factors that shape the effectiveness of dynamic pricing strategies in the digital environment. The purpose of the article is to provide a scientific substantiation of the impact of adaptive pricing on the level of competitiveness of small enterprises in online commerce, taking into account the technological, economic and behavioral factors that determine the effectiveness of dynamic pricing strategies in the digital environment. The paper uses the methods of literature review, comparative analysis, empirical research, and data analysis to identify the problems associated with the implementation of adaptive pricing in small enterprises. The analysis of technical, organizational and informational barriers allowed to identify the main obstacles to the effective application of pricing, as well as to develop recommendations for overcoming them. The study found that the use of adaptive pricing increases the competitiveness of enterprises, allowing them to respond quickly to changes in market conditions and demand. It is determined that the effective use of adaptive pricing allows small companies not only to maintain their market position, but also to increase their share by personalizing price offers and improving customer service. The practical value of the work lies in the development of recommendations for optimizing adaptive pricing processes for small enterprises, which will significantly improve the efficiency of pricing strategies with limited resources. Prospects for further research include improving tools for automating pricing processes and market monitoring methods for small companies.